Hubungan Dan Kefungsian Kekeluargaan Dalam Konteks Keluarga Poligami - Abd Razak, Muhammad Ajib (2021)
The objective of the current study is to explore family relationships and functionality in the context of polygamous families and guided by positive psychology. A qualitative study by thematic analysis approach was carried out to answer four specific research questions: (1) What are the pattern of relationship in the context of polygamous families? (2) What are the patterns of quality and satisfaction of the polygamous families? (3) How do the family members evaluate the polygamy in terms of adaptation and family cohesiveness? (4) How do polygamous families function in the general context? A total of 21 respondents from six polygamous families around the state of Selangor were chosen to be interviewed based on the purposive sampling. In-depth interviews were conducted face-to-face. The collected data were transcribed and analyzed manually. The analyzed were done based on the categories of husbands, wives, and children. The study found six types of theme of polygamous family relationships, namely 1) the relationship between family members is dynamic (unstable), 2) family members are always supportive of each other, 3) family relationships are moving towards better adaptation, 4) conflicts in polygamous families are unique, 5) polygamous families use open communication, and 6) trust between family members is inconsistent.